Training as a determiner of competitive powner and human resources - Anis Eliyana, Amalia, Anis Elyana, (Opción, 2019)
The aim of the study is to investigate training as determiner of competitive power and human resources. This study uses qualitative approach and focuses on creating human resource development to improve competitiveness. As a result, competence-based human resource development may benefit both employees, organizations, industries, regional and national economies. In conclusion, development of competence-based human resources are conducted in order to provide results in accordance with the goals and objectives of the organization determined with the standards.